About couses for the in su lar localization of spruce forests in Polissya - Melnyk, V.I. (Reports of the National Academy of Sciences of Ukraine, 2020)
Insular spruce forests of Polissya are a extrazonal dark coniferous phytocenosis located among the boreal and Carpathians continuous regions of Picea abies (L.) Karst. area. In spite of a small participation in the forest fund, they could be interesting for forestry, since they differ by the high genetically determined productivity. Insular Polissya’s spruce forests are included into the Green Book of Ukraine. Some rare boreal species of the flora of spruce forests are listed in the Red Data Book of Ukraine. An actual problem is the development of a scientific foundations of the conservation of Polissya’s spruce forests under the global warming conditions. Controversial and one of the most interesting in theoretical sense is the question about the causes for the insular localization of spruce forests in Polissya. An survey and critical analysis of the hypotheses are given, and the original theory of spruce forests localization in Polyssya is set out. Insular localization of spruce forests in Polissya is connected with the inconsistency of prevailing edaphotops of the region (weakly moisture-intensive sandy soils and water-logged peat bogs) to the ecological needs of spruce seedlings. For normal physiological functions of seedlings, the soil moisture near the surface is needed in the limits from 30 to 80 % of the total moisture capacity. Only in ecotones among forest and swamp ecosystems, soil moisture near the surface regularly stays within the tolerance zone of spruce seedlings. Only under such conditions, it is possible the continuously generated change in populations of the Norway spruce and, consequently, the very existence of autochthonous spruce forests. So far as autochthonous spruce forests are primary rare stenotopic communities, confined to ecotones with specific soil moisture, the widespread invasion of the Norway spruce into surrounding forest formations is excluded. Caused by the drainage reclamation in adjacent territories, the hydrological change in habitats of Picea abies ln Polissya leads to the violation of population’s stability. So, the surface of soils cannot provide a moisture required for the spruce seedlings. As a result, regressive populations might be formed, which are doomed to complete the degradation. An intensive invasion of the hornbeam (Carpinus betulus L.) occurs on the ecological niches released from the spruce. During the invasion of bark beetles in insular spruce forests, it is necessary to remove fallen dead trees, but to leave ecotones unchanged.